(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Twenty-two lines were crossed with 2 testers in a Line × Tester mating design in 2017-18 and the resulting 44 crosses along with the lines, testers and three checks i.e., BARI Hybrid Maize 9 (BHM 9), 981 and Elite were evaluated in a alpha lattice design with two replications, during rabi, 2018-19. Highly significant differences were found among the genotypes for all the characters studied. Parent and parents vs crosses were significant for all the characters except ASI indicating greater diversity in the parental lines of the traits. Three lines (viz., BMZ 55, BMZ 53, BMZ 4) showed significant negative GCA effect for both days to 50% tasseling and silking, indicating good general combiners for earliness. BMZ 15, BMZ 55, BMZ 53 and BMZ 68 showed significant negative GCA effects for both plant and ear height. BIL 79, Pinacle 17 and BIL 182 exhibited desirable significant positive GCA for grain yield. Considering desirable GCA effects those parents could be used extensively in hybrid breeding program to accumulate those favorable genes. However, two cross combinations BIL 182 x CML 429 and BIL 79 x CML 429 were found promising considering SCA effect, mean performance and could be utilized for enhancing hybrid production. Considering BHM 9 as check, the percent standard heterosis for grain yield varied from -52.6 to 0.6%. None of the crosses showed significant positive heterosis for grain yield except BIL 79 × CML 429. Bangladesh J. Agril. Res. 46(3): 261-274, September 2021